Effect of fermentation on antioxidant contents, antioxidant activity, and mineral contents of Cleome gynandra leaves - Shafie, Nurul Husna; Chung, Ya Ching (Universiti Putra Malaysia Press, 2023)
C. gynandra provides medicinal benefits due to nutritional properties. This study aimed to determine the effect of fermentation on antioxidant properties and mineral contents of C. gynandra. The findings showed that fresh C. gynandra had the highest total phenolic content (60.44±3.14 mg GAE/g extract), followed by commercial fermented (49.48±1.88 mg GAE/g) and self-fermented (7.89±0.83 mg GAE/g). Fresh C. gynandra also showed the highest scavenging activity (66.01±1.14%) compared to both fermented samples. The fresh sample had the highest minerals content except sodium. Fermentation might reduce the antioxidants and minerals in C. gynandra.